2018
DOI: 10.1163/22134808-00002586
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Playback Rate of Audiovisual Speech Leads to a Surprising Decrease in the McGurk Effect

Abstract: We report the unexpected finding that slowing video playback decreases perception of the McGurk effect. This reduction is counter-intuitive because the illusion depends on visual speech influencing the perception of auditory speech, and slowing speech should increase the amount of visual information available to observers. We recorded perceptual data from 110 subjects viewing audiovisual syllables (either McGurk or congruent control stimuli) played back at one of three rates: the rate used by the talker during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Many factors, including co-articulation (number of repetitions of the syllable, i.e., ba vs. baba ) and speech rate (fast vs. slow) may contribute to the efficacy of a given McGurk exemplar (Magnotti et al, 2018a, b). In the absence of techniques for psychometrically manipulating McGurk stimuli as there are for simpler sensory stimuli (such as parametrically changing the volume of a tone to measure auditory sensitivity) participants in the present study viewed a battery of nine different ba/ga and pa/ka McGurk exemplars, with the average score across stimuli measuring the overall susceptibility of a given participant to the illusion.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, including co-articulation (number of repetitions of the syllable, i.e., ba vs. baba ) and speech rate (fast vs. slow) may contribute to the efficacy of a given McGurk exemplar (Magnotti et al, 2018a, b). In the absence of techniques for psychometrically manipulating McGurk stimuli as there are for simpler sensory stimuli (such as parametrically changing the volume of a tone to measure auditory sensitivity) participants in the present study viewed a battery of nine different ba/ga and pa/ka McGurk exemplars, with the average score across stimuli measuring the overall susceptibility of a given participant to the illusion.…”
Section: Discussionmentioning
confidence: 99%
“…One concern about online data collection that is particularly relevant to audiovisual speech experiments is that poor auditory or visual quality may cloud effects that would be observable in a laboratory setting (but see [ 14 , 101 ] for other examples of online studies on the McGurk effect). To address this issue, we ensured that participants had sufficiently good auditory equipment by employing a recently introduced headphone screening [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causal inference of multisensory speech (CIMS) model incorporates these processes into a principled framework that predicts perception of arbitrary combinations of auditory and visual speech (Magnotti and Beauchamp, 2017). The CIMS model has been used to explain a number of puzzling audiovisual speech phenomena, such as the increase in the McGurk effect observed with co-articulation (Magnotti et al, 2018b); the decrease in the McGurk effect observed with slower playback rates (Magnotti et al, 2018a); and why the McGurk effects is produced by some incongruent syllables but not others (Magnotti and Beauchamp, 2017 (Alsius et al, 2018;Rosenblum, 2019).…”
Section: Introductionmentioning
confidence: 99%